Exploration of Creativity Through Project-Based Learning in Eco-Printing Using the Pounding Technique for Students at Kalanganyar Public Elementary School Sidoarjo - Khoirotul Amaliyah; Raya Sulistyowati; Surya Andhini; Mei Nurkholifah; Tutut Putri Ramadani; Vinky Aurelia Putri Yuniar; Cynthia Maharani (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Exploration to develop elementary school students' creativity through the application of Project-Based Learning (PBL) with pounding-based Ecoprint techniques at Kalanganyar State Elementary School, Sidoarjo. The Ecoprint program at Kalanganyar Elementary School is an initiative that involves college students teaching grade 7 to develop children's creativity. Ecoprint activities involve a process of creating environmentally friendly batik fabric that emphasizes sustainability principles. In this activity, leaves, flowers, or other organic materials are used as natural motifs on batik fabric by pressing them directly onto the fabric surface. In this program, students in grades 4, 5, and 6 at Kalanganyar Elementary School are invited to explore the beauty of nature through Ecoprinting using the pounding technique, which utilizes natural materials to print environmentally friendly artworks. In this process, children not only learn about printing techniques but also important values such as environmental sustainability, respect for nature, and responsibility towards the environment. They are given the opportunity to develop their creativity by creating designs inspired by their surroundings. The program employs an approach that includes problem identification, preparation, coordination with parents and the community, activity socialization, program inauguration, and implementation. Through this activity, it is hoped that children can broaden their understanding of the importance of preserving the environment from an early age and develop critical and creative attitudes in addressing ecological challenges in the future. Additionally, the Ecoprint program also provides opportunities for children to collaborate, receive additional training, and build positive relationships with the surrounding community. This is expected to help them grow into caring, independent young people who make positive contributions to sustaining our environment.